How Linguistic Framing Affects Factory Workers' Initial Trust in Collaborative Robots: The Interplay Between Anthropomorphism and Technological Replacement. Issue 158 (February 2022) - Kopp, Tobias; Baumgartner, Marco; Kinkel, Steffen
Highlights: Linguistic framing provides an effective means for increasing initial trust in collaborative robots Effects of anthropomorphism on trust are moderated by the human-robot relation (cooperative vs. competitive) Research designs in the industrial context need to consider the psychology of technological replacement External validity is ensured by recruiting factory workers as an adequate sample for industrial human-robot interaction Abstract: An appropriate level of human-robot trust is considered a necessary precondition for successful human-robot interaction (HRI). With collaborative robots (cobots) entering production sites and allowing factory workers to operate interactively, issues of human-robot trust at the workplace are gaining relevance and complexity. It is widely believed that trust is promoted by anthropomorphisation, that is, the application of human-like mental models to technical devices. Anthropomorphisation can be triggered by altering either the characteristics of the robot or the mental models of the human interaction partner, for example by providing linguistically framed descriptions of the robot. However, the research base on linguistic framing effects on anthropomorphisation and on human-robot trust in industrial environments is scarce. This article aims to close this research gap by investigating changes in inexperienced factory workers' initial trust induced by linguistic framing in the run-up to an interaction. Besides the human-likeness of the robot, the framing also addresses the human-robot relation in order to take into account the special circumstances of cobot use in the industrial workplace. In this usage context, cobots frequently provoke ambivalent attitudes amongst employees, who see themselves in a cooperative or in a competitive relationship to the robot, depending on whether they consider the latter as complementing or substituting their jobs. The results of the pre-post online experiment presented in this article highlight the effectiveness of framing and reveal a significant interaction effect between perceived human-likeness and cooperativeness. In particular, human-like framing of the cobot significantly increases an employee's trust in the cobot only when the human-cobot relation is perceived as cooperative. This can be explained by different psychological reactions on the anticipated technological replacement by either man or machine. This finding suggests that the way employees relate to cobots represents a relevant contextual factor in the industrial workplace that moderates the effect of anthropomorphisation on human-robot trust. Furthermore, providing information about the cobot generally seems to foster trust, possibly resulting from an effect of imagined contact with the cobot.